The effects of environmental regulations on the sustainable entrepreneurship from the perspective of dynamic capabilities: a study based on Chinese new energy enterprises - Peng, Huatao; Pan, Yueyi (Frontiers in Energy Research, 2024)
Environmental regulations play important roles in the enterprise's sustainable entrepreneurship, and their relationships are affected by the enterprise's dynamic capabilities. This paper analyzed the panel data of China's new energy industry from 2011 to 2021, aiming to explore the impact of environmental regulations on sustainable entrepreneurship and the mechanism of dynamic capacity between them. The results documented that: (1) There was an inverted U-shaped relationship between incentive environmental regulation and enterprise's sustainable entrepreneurial performances, and a positive relationship between command environmental regulations and enterprise's sustainable entrepreneurial performances; (2) The absorptive capacity of dynamic capacities negatively moderated the inverted U-shaped relationship between incentive environmental regulations and sustainable entrepreneurial performances, and negatively moderated the positive relationship between command environmental regulations and sustainable entrepreneurial performances; (3) The innovative capability of dynamic capabilities negatively moderated the inverted U-shaped relationship between incentive environmental regulations and sustainable entrepreneurial performances, and negatively moderated the positive relationship between command environmental regulations and sustainable entrepreneurial performances; (4) The adaptive ability of dynamic capabilities had no moderating effect between the two environmental regulations and sustainable entrepreneurial performances. Based on the results, two enlightenment suggestions were put forward: For relevant government departments, the formulation and implementation of environmental regulations need to be adapted to local conditions; For new energy start-ups, the deployment of dynamic capabilities vary depending on policies and resources. The contributions of this paper include the following two aspects. Firstly, it corrects the inherent logic between environmental regulations and sustainable entrepreneurships to some extent, expands the research field of dynamic capabilities. Secondly, it provides a certain enlightening effect on the formulation of environmental regulation policies and the application of the enterprise's dynamic capabilities.